A Decalogue to Avoid Routine Ileostomy in Selected Patients With Border Line Risk to Develop Anastomotic Leakage After Minimally Invasive Low-Anterior Resection: A Pilot Study. (February 2020) - Morales-Conde, Salvador; Alarcón, Isaias; Yang, Tao; Licardie, Eugenio; Balla, Andrea
Purpose . Protective ileostomy (PI) during anterior resection (AR) for rectal cancer decreases the incidence of anastomotic leakage (AL) and its subsequent complications, but it may itself be the cause of morbidity. The aim is to report our protocol in the management of selected patients with borderline risk to develop AL after laparoscopic AR and ghost ileostomy (GI) creation. Methods . Patients who underwent AR were stratified based on the risk to develop AL. Steps to avoid PI were splenic flexure mobilization, reduced pelvic bleeding, to employ different stapler charge if neoadjuvant chemo-radiotherapy is performed, to perform a horizontal section of the rectum, to evaluate the anastomotic vascularization with a fluorescence angiography, to perform a side-to-end anastomosis, intraoperative methylene blue test, pelvic and transanal drainage tubes placement, and the GI creation. After surgery, inflammatory blood markers were monitored to detect potential leakages. Results . Twelve patients were included. In one case, the specimen proximal section was changed after fluorescence angiography. There were no conversions in this group of patients. One postoperative AL occurred and was treated with radiological drainage placement, not being necessary to convert the GI. PI was avoided in 100% of cases. Conclusions . Patients' characteristics cannot be changed, but several steps were used to avoid routine PI creation. The present protocol could be a valuable option to avoid PI in selected patients. Further studies with a wider sample size, and defined criteria to stratify the patients based on the risk to develop AL, are required.